High-Dose Acetaminophen Alters the Integrity of the Blood-Brain Barrier and Leads to Increased CNS Uptake of Codeine in Rats - Junzhi Yang; Robert D. Betterton; Erica I. Williams; Joshua A. Stanton; Elizabeth S. Reddell; Chidinma E. Ogbonnaya; Emma Dorn; Thomas P. Davis; Jeffrey J. Lochhead; Patrick T. Ronaldson (MDPI AG, 2022)
The consumption of acetaminophen (APAP) can induce neurological changes in human subjects; however, effects of APAP on blood-brain barrier (BBB) integrity are unknown. BBB changes by APAP can have profound consequences for brain delivery of co-administered drugs. To study APAP effects, female Sprague-Dawley rats (12-16 weeks old) were administered vehicle (i.e., 100% dimethyl sulfoxide (DMSO), intraperitoneally (i.p.)) or APAP (80 mg/kg or 500 mg/kg in DMSO, i.p.; equivalent to a 900 mg or 5600 mg daily dose for a 70 kg human subject). BBB permeability was measured via in situ brain perfusion using [14C]sucrose and [3H]codeine, an opioid analgesic drug that is co-administered with APAP (i.e., Tylenol #3). Localization and protein expression of tight junction proteins (i.e., claudin-5, occludin, ZO-1) were studied in rat brain microvessels using Western blot analysis and confocal microscopy, respectively. Paracellular [14C]sucrose "leak" and brain [3H]codeine accumulation were significantly enhanced in rats treated with 500 mg/kg APAP only. Additionally, claudin-5 localization and protein expression were altered in brain microvessels isolated from rats administered 500 mg/kg APAP. Our novel and translational data show that BBB integrity is altered following a single high APAP dose, results that are relevant to patients abusing or misusing APAP and/or APAP/opioid combination products.